Drug-Metabolizing Enzymes in Pharyngeal Mucosa and in Oropharyngeal Cancer Tissue - Ullrich, Dieter; Münzel, Peter A; Beck-Gschaidmeier, Simone; Schröder, Michael; Bock, Karl Walter (Biochemical pharmacology, 1997)
Cytochrome P4501A1 (CYP1A1) and the UDP-glucuronosyltransferase isoform UGT1A6 were studied in pharyngeal mucosa and squamous cancer tissue obtained from 27 male subjects (10 healthy nonsmoking volunteers, 10 smokers, and 7 smokers with pharyngeal cancer). CYP1A activity (7-ethoxyresorufin O-deethylase) was significantly induced in smokers as compared to nonsmokers (2.3 ± 1.1 and 0.8 ± 0.4 pmol · min −1 · mg protein −1, respectively). Immunoblot analysis demonstrated enhanced CYP1A1 protein in smokers. UGT activity towards 4-methylumbelliferone and 1-naphthol was also detectable in oropharyngeal mucosa. RT-PCR (reverse transcriptase-polymerase chain reaction) analysis indicated that UGT activity was at least in part due to the expression of UGT1A6. In cancer tissue, CYP1A activity was decreased in comparison with surrounding healthy mucosa (1.2 ± 0.9 in tumor tissue vs. 2.2 ± 0.7 pmol · min −1 · mg protein −1, respectively), whereas means and medians of UGT activity were unchanged. The results suggest that phase I and II drug-metabolizing enzymes are detectable in oropharyngeal mucosa and that CYP1A activity is inducible by constituents of cigarette smoke.